Dynamics of the Implementation of the Red and White Cooperative Program and Its Implications for Community Social Welfare: A Qualitative Study in Jrebeng Kulon Village, Probolinggo City - Ayyubi, Ahmad Maman; Marwiyah, Siti; Yunus, Eko Yudianto (Prodi Ilmu Politik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Islam Negeri Sunan Ampel Surabaya, 2026)
This study analyzes the implementation of the Merah Putih Cooperative Program and its implications for social welfare in Jrebeng Kulon Village, Probolinggo City. A qualitative descriptive approach was employed to examine the policy implementation process using Edward III’s framework, which emphasizes communication, resources, disposition, and bureaucratic structure. Data were collected through in-depth interviews, observations, and document analysis with purposively selected informants. The findings reveal that the program has not yet been implemented optimally. Policy communication remains inconsistent, limiting public understanding and participation. Resource constraints, including inadequate human resource capacity, financial capital, and infrastructure, have hindered the cooperative’s development. Although implementers demonstrate commitment, their efforts are constrained by limited innovation and adaptive capacity. In addition, weak coordination among stakeholders and fragmented governance mechanisms reduce implementation effectiveness. Despite these challenges, the program has improved community access to basic necessities and small-scale financial services, contributing to local social welfare. The findings underscore the interdependence of implementation variables and highlight the need for stronger institutional coordination, resource capacity, and policy communication to achieve sustainable social welfare outcomes.